Empowerment of brides-to-be in an effort to prevent stunting events early through balanced nutrition - Mardiana, Mardiana; Dwi Rokhmah, Farida; Ulfa, Maria; Setyaningsih, Aryanti; Palgunadi, Palgunadi; Nurul Khidmah, Alfi; Salsabila, Jovita; Ardiyansyah, Raditya; Rafkhani, Tesa (Journal Pengabdian Masyarakat Politeknik Sandi Karsa, 2025)
Stunting, a condition of impaired growth and development among children under five caused by chronic malnutrition in the first 1,000 days of life, remains a significant public health issue in Indonesia. Early prevention efforts are essential, particularly among women of reproductive age and prospective brides and grooms, who are critical in ensuring optimal maternal and child health. This community service program was conducted at Puskesmas Sekaran, Semarang, to empower prospective couples through balanced nutrition education to reduce the risk of stunting. The program adopted a participatory approach involving health workers, village authorities, and the Office of Religious Affairs. Activities included baseline assessments of chronic energy deficiency (CED) and anemia, development of educational media (booklets, leaflets, and banners), pre-marital nutrition classes, and intensive student mentoring. The intervention reached 25 participants across five villages, with activities delivered interactively through presentations, discussions, and Q&A sessions addressing scientific facts and common myths about nutrition. Pre- and post-tests were used to evaluate changes in knowledge, showing significant improvements: average pre-test scores increased from 89/100 to 95/100, with 92% of participants demonstrating improved knowledge and 76% achieving perfect post-test scores. These findings highlight that nutrition education, supported by user-friendly media, effectively enhances knowledge and awareness regarding balanced nutrition among prospective brides and grooms. The program demonstrates that empowering couples before marriage contributes to healthier pregnancy preparation, reduces risks of CED and anemia, and ultimately supports the national goal of lowering stunting prevalence.